Oat bran fortified raspberry probiotic dairy drinks: Physicochemical, textural, microbiologic properties, in vitro bioaccessibility of antioxidants and polyphenols. (October 2021) - Savas, Busra Sena; Akan, Ecem
Abstract: In this study, it was aimed to determine the effects of oat bran, which is a good source of dietary fiber, on L. acidophilus, L. casei and B. lactis viability, physicochemical, textural, sensorial properties, total phenolic compound and antioxidant activity with DPPH, CUPRAC and ABTS method of probiotic dairy drinks. In addition, the effects of in vitro gastrointestinal digestion on bioaccessibility of phenolic and antioxidant compounds were investigated. Oat bran only significantly increased B. lactis viability. There were no significant differences on viscosity, water holding capacity and antioxidant activity of samples during the 21 day of storage period. Oat bran did not significantly affect the total phenolic compound and antioxidant activities of samples. After in vitro gastrointestinal digestion, the total phenolic compounds of all samples increased (p<0.05). While the total phenolic compound recovery value after in vitro digestion was quite high (109–192%), bioaccessibility of antioxidant compounds varied according to the antioxidant activity method. In conclusion, although oat bran did not show the expected effects on probiotic dairy drinks, the use of oat bran together with raspberry did not have a negative effect on probiotic drinks and they can be consumed as a functional food with good antioxidant properties in diet.